2016
DOI: 10.1007/s00284-016-1046-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mono and Di-rhamnolipids on Biofilms Pre-formed by Bacillus subtilis BBK006

Abstract: Different microbial inhibition strategies based on the planktonic bacterial physiology have been known to have limited efficacy on the growth of biofilms communities. This problem can be exacerbated by the emergence of increasingly resistant clinical strains. Biosurfactants have merited renewed interest in both clinical and hygienic sectors due to their potential to disperse microbial biofilms. In this work, we explore the aspects of Bacillus subtilis BBK006 biofilms and examine the contribution of biologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 21 publications
1
18
0
3
Order By: Relevance
“…These results are also in agreement with previous findings (Davey et al 2003). Other studies have also implicated rhamnolipids with antimicrobial and antibiofilm inhibitions (Das et al 2014;D ıaz De Rienzo and Martin 2016b). Regarding LSLs, a recent review on the application of biosurfactants for oral health applications (Elshikh et al 2016a), concluded that these biomolecules had not been investigated thoroughly.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results are also in agreement with previous findings (Davey et al 2003). Other studies have also implicated rhamnolipids with antimicrobial and antibiofilm inhibitions (Das et al 2014;D ıaz De Rienzo and Martin 2016b). Regarding LSLs, a recent review on the application of biosurfactants for oral health applications (Elshikh et al 2016a), concluded that these biomolecules had not been investigated thoroughly.…”
Section: Discussionsupporting
confidence: 89%
“…Treatment of immature biofilm with biosurfactants has shown promising results, with most bacterial biofilms disrupted at concentrations as low as 200 μ g ml −1 . This efficacy, beside the direct killing effect of biosurfactants on the bacteria, can be explained in terms of the ability of the biosurfactant to disrupt the biofilm matrix, as has been demonstrated (Díaz De Rienzo and Martin ). This opens a new avenue for using biosurfactant in adjuvant therapy, to reduce dosage of antibiotics and to enhance efficacy (Kasturi and Prabhune ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, while normal rhamnolipid concentrations are important for the maintenance of mature biofilms, particularly for fluid channel maintenance and cellular migration, elevated levels cause biofilm dispersal for a range of bacterial species [109,110,111,112]. …”
Section: Dispersal Moleculesmentioning
confidence: 99%
“…In addition, rhamnolipids play a role in promoting microcolony formation in the initial phases and in maintaining channels between multicellular structures in biofilms in the later phases of biofilm development (Pamp and Tolker-Nielsen, 2007). P. aeruginosa rhamnolipids can also act on biofilm dispersal in other species, such as Bordetella bronchiseptica, B. subtilis and S. epidermidis (Irie et al, 2005;Pihl et al, 2013;De Rienzo and Martin, 2016). A recent study showed that rhamnolipids produced by P. aeruginosa have another function in biofilm dispersal: by acting in cooperation with the P. aeruginosa QS compound N-(3-oxo-dodecanoyl) homoserine lactone to disperse E. coli biofilms, they play a critical role in an interspecies chemical signaling pathway (Bhattacharjee et al, 2016).…”
Section: Effectors Promoting Biofilm Dispersalmentioning
confidence: 99%